2022
DOI: 10.1038/s41598-022-18667-x
|View full text |Cite
|
Sign up to set email alerts
|

Fungal succession on the decomposition of three plant species from a Brazilian mangrove

Abstract: Leaf decomposition is the primary process in release of nutrients in the dynamic mangrove habitat, supporting the ecosystem food webs. On most environments, fungi are an essential part of this process. However, due to the peculiarities of mangrove forests, this group is currently neglected. Thus, this study tests the hypothesis that fungal communities display a specific succession pattern in different mangrove species and this due to differences in their ecological role. A molecular approach was employed to in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Fungi, particularly Ascomycota and Basidiomycota, were more abundance in the lower layer, suggesting their role in the decomposition of organic matter in marine sediments (Moitinho et al, 2022). Our observations regarding the prevalence of archaea are consistent with those of Schorn et al (2022), who also reported a higher abundance of archaea in deeper sediment layers.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Fungi, particularly Ascomycota and Basidiomycota, were more abundance in the lower layer, suggesting their role in the decomposition of organic matter in marine sediments (Moitinho et al, 2022). Our observations regarding the prevalence of archaea are consistent with those of Schorn et al (2022), who also reported a higher abundance of archaea in deeper sediment layers.…”
Section: Discussionsupporting
confidence: 88%
“…In the lower layers, their high abundance could be influenced by the reshuffling of the top sediment layer with each tide. Fungi, particularly Ascomycota and Basidiomycota, were more abundance in the lower layer, suggesting their role in the decomposition of organic matter in marine sediments (Moitinho et al, 2022). Our observations regarding the prevalence of archaea are consistent with those of Schorn et al .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is also suspected that Rhizophora mucronata has thinner leaves, hence, it is easier to decompose. The length of time required is influenced by several factors, including mangrove type, environmental conditions and organic moisture, organic equilibrium and excess microorganisms on mangrove leaves that can affect mangrove litter decomposition (Vinh et al, 2020;Moitinho et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Litter is dead plant parts such as leaves, twigs, flowers, barks, and roots that spread on the soil surfaces before decomposing (Pradisty et al, 2021;Zhang et al, 2021). Mangrove leaf litter can be decomposed by fungi and bacteria into nutrients and litter particles which serve as food source for fishes, shrimps, and crabs (Robertson., 1988;Moitinho et al, 2022). Macrobenthos and herbivorous biota are some of the early decomposers that will destroy or chop the remains of the leaves into smaller parts which then will be released back as feces.…”
Section: Introductionmentioning
confidence: 99%
“…Fungal succession, which refers to different species that become dominant at different points in time, is one of the most widespread and universal patterns of community assembly and activity in the ecosystem’s ecology [ 20 ]. Although fungal succession on various plant substrates has been well explored [ 21 , 22 , 23 , 24 , 25 ], it has received little attention when it comes to bamboo. Zhou and Hyde [ 26 ] placed several bamboo culms in terrestrial habitats in Hong Kong and investigated their fungal succession on bamboo via culturing on a medium and observing fruit bodies under a microscope in the laboratory.…”
Section: Introductionmentioning
confidence: 99%